2023
DOI: 10.3389/fcell.2023.1193765
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages—bone marrow mesenchymal stem cells crosstalk in bone healing

Abstract: Bone healing is associated with many orthopedic conditions, including fractures and osteonecrosis, arthritis, metabolic bone disease, tumors and periprosthetic particle-associated osteolysis. How to effectively promote bone healing has become a keen topic for researchers. The role of macrophages and bone marrow mesenchymal stem cells (BMSCs) in bone healing has gradually come to light with the development of the concept of osteoimmunity. Their interaction regulates the balance between inflammation and regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 169 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…The etiology of osteoporosis is mainly the imbalance between bone formation mediated by osteoblasts and bone resorption mediated by osteoclasts, which results in bone loss because of a decreased bone formation/bone resorption ratio, , so that by inhibiting osteoclast-mediated bone resorption to a certain extent, osteoporosis can be treated by inhibiting osteoclast-mediated bone resorption . Osteoclasts are derived from bone marrow macrophages (BMMs) differentiated from hematopoietic cell lineages, , so we first confirmed whether these acquired FRT0-derived peptides exhibit cytotoxicity against BMMs. On the basis of the results of the CCK8 test, no significant cell death was observed even when up to 20 μM of the peptide was added to the culture medium (Supplementary Figure 3).…”
mentioning
confidence: 83%
“…The etiology of osteoporosis is mainly the imbalance between bone formation mediated by osteoblasts and bone resorption mediated by osteoclasts, which results in bone loss because of a decreased bone formation/bone resorption ratio, , so that by inhibiting osteoclast-mediated bone resorption to a certain extent, osteoporosis can be treated by inhibiting osteoclast-mediated bone resorption . Osteoclasts are derived from bone marrow macrophages (BMMs) differentiated from hematopoietic cell lineages, , so we first confirmed whether these acquired FRT0-derived peptides exhibit cytotoxicity against BMMs. On the basis of the results of the CCK8 test, no significant cell death was observed even when up to 20 μM of the peptide was added to the culture medium (Supplementary Figure 3).…”
mentioning
confidence: 83%
“…This phenomenon could be attributed to the fact that LA released from the LA hydrogel enhanced the secretion of BMP-2 in osteoblasts differentiated from BMSCs, and the secreted BMP-2 further stimulates the BMSCs to differentiate into osteoblasts. 55,56 Moreover, the expression levels of osteogenesisrelated genes in the LA gel group were slightly higher than those in the control group after incubation for 4 and 7 days (Figure 5g−j). The above results indicated that the LA hydrogel exhibited a certain osteogenic effect, albeit weak.…”
Section: Inhibitory Effect Of Hydrogels On Osteoclastsmentioning
confidence: 95%